Stimuli‐Responsive Materials: Enzyme‐Responsive Nanoparticles for Targeted Accumulation and Prolonged Retention in Heart Tissue after Myocardial Infarction (Adv. Mater. 37/2015). (1st October 2015) - Nguyen, Mary M.; Carlini, Andrea S.; Chien, Miao‐Ping; Sonnenberg, Sonya; Luo, Colin; Braden, Rebecca L.; Osborn, Kent G.; Li, Yiwen; Gianneschi, Nathan C.; Christman, Karen L.
<x xml:space="preserve">Abstract</x> Stimuli‐responsive nanoparticles, when injected systemically, circulate in the blood stream until reaching the site of myocardial infarction (MI). As reported by N. C. Gianneschi, K. L. Christman, and co‐workers on page 5547, recognition by infarct‐associated enzymes induces a morphology transition, triggering the subsequent aggregation of nanoparticles at the site of damage. The resulting microscale aggregates exhibit prolonged retention in the infarct, thereby providing a potential platform for delivering therapeutics to an acute MI.